Evaluating interaction design and user experience in augmented reality: a systematic review - Hughes, Claire L.; Karwowski, Waldemar (Frontiers in Virtual Reality, 2025)
BackgroundAugmented Reality (AR) technologies are rapidly advancing, offering new opportunities for interactive and immersive user experiences. However, the success of AR applications depends significantly on thoughtful interaction design and robust evaluation of user experience (UX). While conventional WIMP (Windows, Icons, Menus, Pointer) interfaces have dominated interface design, they present notable limitations in spatial, embodied environments like AR.ObjectivesThe main purpose of the current paper is to systematically review the state of AR interaction design and UX evaluation, with particular focus on the use of natural versus WIMP-based interaction paradigms. This review aims to assess how different interaction methods are implemented and evaluated, identify underexplored areas, and offer recommendations to guide future AR research and development. Methods: In this systematic review, Compendex, Web of Science, ScienceDirect, ACM Digital, IEEE, and Springer Computer Science were systematically queried for journal articles in order to explore the relationship between interaction design and user experience in AR. Following PRISMA guidelines, 86 peer-reviewed journal articles published between 2013 and 2024 were included based on predefined inclusion and exclusion criteria. Data were extracted and analyzed in terms of context of use, device types, interaction methods, and UX evaluation strategies.ResultsThe findings show that natural interactions, such as gesture, voice, and gaze, are increasingly favored in AR research due to their alignment with spatial and embodied interaction needs. Hybrid systems combining natural and WIMP elements were the most common, with natural components driving the experiential benefits. UX evaluation in AR remains heavily reliant on self-reported measures, with questionnaires like SUS and NASA-TLX dominating. Objective and physiological assessments were rarely used. Usability and cognitive load were the most frequently evaluated UX aspects, while immersive, social, and emotional dimensions remain significantly underexplored. Head-worn displays (HWDs), particularly HoloLens 2, were the most studied devices, although mobile platforms also played a major role in accessible AR design.ConclusionThis review provides insight into how UX is being considered in AR system development and highlights key trends, strengths, and gaps in current research. It underscores the need for more diverse evaluation methods and a broader focus on underrepresented experiential dimensions. By adopting mixed-method approaches and prioritizing user-centered, context-aware interaction paradigms, future AR systems can become more intuitive, inclusive, and effective across a range of application domains.